Sistem Monitoring Pakan dan Air Minum Burung Peliharaan Pemakan Biji Berbasis Internet Of Things - Thauty, Achmad Gildas; Ariessaputra, Suthami; Muvianto, Cahyo Mustiko Okta (DIELEKTRIKA, 2024)
Grain-eating songbirds are often kept as a hobby. These birds have beautiful feather colors and melodious voices. One of the obstacles to maintaining songbirds is that the owner needs more time. The owner is busy working and going out of town, which can cause the bird not to get adequate feed and water, and the owner is also unable to monitor the health condition of the bird. Based on this, a songbird feeding and monitoring system based on IoT was created to monitor the remaining food and drinks in the tank using NodeMCU ESP32 as a system control and data sender to the internet. The system can provide feed and drinking water for pet birds automatically and is connected via the internet to Blynk to send monitoring results. Based on monitoring results, the feed consumption of seed-eating songbirds is 4.74 grams daily, equivalent to 43.14% of the bird's body weight.